Designing a computerized program to evaluate the quality of banking service from the viewpoints of managers and customers - Akram Mohsen Al-Yasiri; Haider Mohammed Kareem (Iraqi Journal for Administrative Sciences, 2025)
The study aims to design a computerized program to evaluate the quality of banking service to be presented to several parties, including: banking departments at their various levels, as well as investors and other relevant parties. The program aims to diagnose the weakness in performance that was identified through field interviews in Iraqi banks before commencing the study. And the lack of software standards to diagnose malfunctions and measure the quality of banking service in preparation for addressing them. The criteria that obtained the highest percentage of agreement between writers and researchers were relied upon, which are (reliability, responsiveness, empathy, and tangible reliability), through two questionnaire forms that we prepared for this purpose, each of which included (30) questions, with six questions for each criterion, formulated according to a five-point Likert scale. The first form was directed to managers, department heads, and employees with experience in the banks in the study sample, numbering (120), and the other form was directed to the customers of the banks in the study sample, numbering (210). The program was implemented in six Iraqi government and private banks, as it was found that the majority of opinions were close From the perspectives of managers and customers, the study reached a number of conclusions, the most important of which are: Weakness in all dimensions of the quality of banking service in the banks sampled by the study. The program is a technology available to users that is characterized by ease and clarity in the process of evaluating and diagnosing the quality of banking service. The study reached several recommendations, including: : Developing all dimensions of the quality of banking service and its causes. We suggest to the Central Bank of Iraq and the general administrations of government and private banks to circulate the program to branch administrations and make it a general program for evaluating the quality of banking service. It is necessary to open training courses for employees to work on modern computerized technologies for the purpose of transforming banking operations from paper to electronic. This increases the efficiency of those operations, reduces the effort, time and costs expended and raises the level of quality of banking service.